2018
DOI: 10.1002/admi.201801206
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Behavior of CH3NH3PbBr3 Single Crystals under Light Illumination

Abstract: Single crystal CH3NH3PbBr3 samples are exposed to light illumination, with a light intensity about seven times stronger than the sun while under ultrahigh vacuum (UHV) conditions, in order to investigate their chemical and structural stability from prolonged light illumination. X‐ray photoemission spectroscopy measurements show that within 10 h of illumination, about half of the initial C, N, and Br elemental concentrations leave the surface and about half of the perovskite's Pb is converted into metallic Pb. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 51 publications
4
34
0
Order By: Relevance
“…X-ray photoemission spectroscopy measurements revealed that, within 10 h, half of the Pb 2 + at the surface had been converted into metallic Pb, whereas C, N, and Br elemental concentration dropped significantly; this resulted in the creation of μm sized voids at the crystal surface, as evidenced by FIB images (Figure 14g). [148] TEM results further showed that single crystals broke apart into nanocrystals upon light exposure, in accordance to previous studies reported the formation of grain boundaries upon aging. [151,152] MAPI SC were found to degrade under UV-light even at temperature as low as 5K and in a similar fashion to PC perovskite.…”
Section: Lightsupporting
confidence: 91%
See 2 more Smart Citations
“…X-ray photoemission spectroscopy measurements revealed that, within 10 h, half of the Pb 2 + at the surface had been converted into metallic Pb, whereas C, N, and Br elemental concentration dropped significantly; this resulted in the creation of μm sized voids at the crystal surface, as evidenced by FIB images (Figure 14g). [148] TEM results further showed that single crystals broke apart into nanocrystals upon light exposure, in accordance to previous studies reported the formation of grain boundaries upon aging. [151,152] MAPI SC were found to degrade under UV-light even at temperature as low as 5K and in a similar fashion to PC perovskite.…”
Section: Lightsupporting
confidence: 91%
“…Reproduced with permission. [148] Copyright 2018, Wiley-VCH. degradation temperature, but suffer from instability related to the existence of the two phases α and δ.…”
Section: Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Light-induced degradation is inevitable against its real application as light absorber in solar cells. [86] Several researchers have reported that sustained illumination caused the decomposition of the perovskite films. [87,88] Moreover, the perovskite material is a structurally soft material compared with c-Si and III-V multi-junction compound (CdTe, GaAs, CIGS) and would decompose by outgassing under high vacuum as encountered in space.…”
Section: High Vacuum With Light Illuminationmentioning
confidence: 99%
“…[15,16] It has been suggested that the internal structure of the MAPbBr 3 crystals is far from perfect due to light-and environment-induced macroscopic voids. [17] Herein, we find that as-synthesized macroscopic MAPbBr 3 crystals exhibit significant presence of chemical contaminants such as oxygen and amorphous carbon, along with a substantial amount of metallic lead (Pb˚), both at their surface and-most intriguingly-deep in the bulk. The Br:Pb ratio is 2.6, instead of 3.…”
Section: Introductionmentioning
confidence: 88%